Towards adult vaccination in India: a narrative literature review - Resham Dash; Ashish Agrawal; Vasant Nagvekar; Jayesh Lele; Alberta Di Pasquale; Shafi Kolhapure; Raunak Parikh (Taylor & Francis Group, 2020)
Despite vast improvements in childhood vaccination coverage in India, adult vaccination coverage is negligible. Our aim was, therefore, to create awareness about the importance of adult immunization. Although the true burden of vaccine-preventable diseases (VPDs) among Indian adults is unknown, adults are particularly vulnerable during outbreaks, due to a lack of immunization, waning immunity, age-related factors (e.g. chronic conditions and immunosenescence), and epidemiological shift. There are no national adult immunization guidelines in India, and although several medical societies have published adult immunization guidelines, these vary, making it unclear who should receive which vaccines (based on age, underlying conditions, etc.). Other barriers to adult immunization include vaccine hesitancy, missed opportunities, and cost. Steps to improve adult vaccination could include: adoption of national guidelines, education of healthcare providers and the public, and promotion of life-course immunization. Improving adult vaccine coverage could help reduce the burden of VPDs, particularly among older adults.